ستراتيجية كياي في ترسيخ قيم الأمانة والانضباط والمسؤولية لدى الطالبات في مدرسة سبيل الروساد الإسلامية الداخلية للبنات في مالانج - Sari , Kiki Widya; Suhartono , Edi; Untari , Sri (JED (Jurnal Etika Demokrasi), 2025)
The urgency of this research arises from the growing concern that character education in Islamic boarding schools has not been systematically examined in terms of concrete strategies used by kiai to internalize honesty, discipline, and responsibility among female students. This study aims to describe and analytically interpret the kiai’s strategies for internalizing these core moral values at Pondok Pesantren Putri Sabilurrosyad Malang. A qualitative single-case study design was employed, involving the caregiver (kiai), boarding school management, and female students as research subjects. Data were collected through observation, in-depth interviews, and questionnaires, and were analyzed using a pattern-matching technique to compare empirical findings with theoretically expected patterns. The findings indicate that honesty is internalized through continuous advice, habituation in daily activities, motivational reinforcement, and the kiai’s personal role modelling. Discipline is fostered by clear rules and regulations, intensive guidance, sustained motivation, and the application of educational sanctions for rule violations. Responsibility is cultivated through direct guidance, moral exhortation, exemplary behaviour of the kiai, and structured obligations such as timely completion of tasks, memorization assignments, and participation in communal worship and environmental care. Overall, these strategies form an integrated moral education system that effectively supports value internalization. The novelty of this research lies in its focused, in-depth mapping of kiai’s strategic roles as director, model, educator, and mentor in a female-only pesantren context using a pattern-matching approach. This study contributes theoretically to Islamic education and character education discourse, and practically offers a contextualized strategic framework for strengthening value-based leadership in Islamic boarding schools.